2015
DOI: 10.1002/lary.25409
|View full text |Cite
|
Sign up to set email alerts
|

The role of routine hearing screening in children with cystic fibrosis on aminoglycosides: A systematic review

Abstract: This systematic review supports a recommendation for clinicians to perform routine hearing screening in children with CF during and after aminoglycoside exposure based on the high prevalence of SNHL in this population. Future studies should define the optimal timing for hearing screening during and after aminoglycoside therapy in children with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Ototoxicity with sensorineural hearing loss due to aminoglycosides occurs at the level of cochlear hair cells secondary to the generation of reactive oxygen specimens [30]. Because hair cells at the basal turn of the cochlea are affected first, high-frequency hearing loss is one of the first findings, occurring as early as 4 hours after treatment [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ototoxicity with sensorineural hearing loss due to aminoglycosides occurs at the level of cochlear hair cells secondary to the generation of reactive oxygen specimens [30]. Because hair cells at the basal turn of the cochlea are affected first, high-frequency hearing loss is one of the first findings, occurring as early as 4 hours after treatment [30].…”
Section: Discussionmentioning
confidence: 99%
“…Ototoxicity with sensorineural hearing loss due to aminoglycosides occurs at the level of cochlear hair cells secondary to the generation of reactive oxygen specimens [30]. Because hair cells at the basal turn of the cochlea are affected first, high-frequency hearing loss is one of the first findings, occurring as early as 4 hours after treatment [30]. Aminoglycoside toxicity might involve a genetic predisposition, at least as a contributing factor: several mitochondrial gene mutations in the MT-RNR1 and MT-TS1 groups (including the mitochondrial 1555a>G mutation) might be culpable [3032], and many studies have compared the efficacy and toxic potential of different regimens of antibiotics in CF patients, with varying results [15, 20, 3234].…”
Section: Discussionmentioning
confidence: 99%
“…Their use is also increasing due to emerging multidrug-resistant pathogens, e.g., in the treatment of cystic fibrosis and tuberculosis (3,7). The long-term daily administration of aminoglycosides required to manage these conditions results in a high incidence of hearing loss, affecting the quality of life (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrate that AG ototoxicity is directly correlated with the number of treatment courses, hence the cumulative dose [10] , [13] , [17] . One recent systematic review including twelve studies conducted between 1979 and 2014 reported an overall SNHL prevalence of 0–29% in CF children treated with aminoglycosides; this was increased to 44% if the number of treatment courses was more than 10 [18] . Also in our study 2 of the 4 patients in the CF group with SNHL had been exposed to more than 8 courses of amikacin.…”
Section: Discussionmentioning
confidence: 99%